Pengaruh Kepuasan Kerja dan Disiplin Kerja terhadap Komitmen Karyawan Generasi Milenial di Kota Palembang - Maria Clarista Dinda Christy; Maria Clarissa Della Christy; Prisilia Cica Cantika (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
Additionally, companies need to understand the characteristics and values that millennial employees uphold, such as flexibility, empowerment, and opportunities to grow. This generation tends to look for jobs that give them room to innovate, as well as the opportunity to achieve a balance between personal and work life. Therefore, policies that support flexible working hours, remote working, and opportunities for skill development relevant to industry developments will be a significant added value for millennial employees. In addition, open and two-way communication between management and employees is also very important. Millennials are more likely to choose a workplace that is transparent and communicative, where they feel valued and have a voice in decision-making. By maintaining good relationships and ensuring that employees feel heard, companies can create a more positive work environment and strengthen employee commitment to the company. The positive influence of job satisfaction and work discipline on employee commitment, especially the millennial generation, can also be seen as a contributing factor to the decline in employee turnover rates. Employees who feel satisfied and have good work discipline tend to be more loyal and have the desire to stay longer in the company. This will certainly reduce recruitment and training costs for companies, while increasing organizational stability in the long run. This research is expected to be a reference for companies in formulating HR strategies that are more adaptive to the needs of millennial employees, which in turn can increase productivity and create a more innovative and sustainable work environment.